A comparative study of endoscopic septoplasty and conventional septoplasty - Deshmukh, Kiran A.; Ambiger, Rashmi T. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The aim of the study was to study the advantages and disadvantages of endoscopic septoplasty and conventional septoplasty and to co-relate the two procedures in terms of intra-operative visualization, duration of surgery, procedural difficulties, hospital stay and complications. Methods: It is a prospective study done during November 2017 to April 2019 on 50 patients with symptomatic deviated nasal septum. Patients were randomly divided into conventional septoplasty and endoscopic septoplasty groups of 25 each. Surgery was performed as according to the division. Followed up on 1st week, 15th day, 1st month and 3rd month. Results: In endoscopic septoplasty group, septal pathology, precise correction of the pathology, with less complications were seen. Hospital stay and duration of surgery were significantly less in endoscopic group. Conclusions: For minimal and posterior deviations of the septum, endoscopic septoplasty is better, whereas for anterior deviations, conventional septoplasty could be better choice.